Ø¯ÙˆØ± Ø§Ù„Ù…Ù†Ø§Ø¸Ø±Ø© Ø¨Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù…ØØ§Ø¯Ø«Ø© Ù„Ø¯Ù‰ Ø§Ù„Ù…ØªÙ†Ø§Ø¸Ø±ÙŠÙ† Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ±Ù‡Ø§ - Shaiful Baharum, Azlan bin; Muhammad, Siti Ilham; Ahmad, Mohammad Imran (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
The speaking skills among students are not satisfying. Thus, this research aims to clarify the role of Arabic debates in developing the speaking skills among non-Arabic speaker debaters. The main purpose of this study is to find out the benefit of Arabic debates in developing the speaking skills among students of Darul Quran JAKIM. It has been using the method of descriptive analysis in the implementation of this academic writing. To gather information, the researcher distributed questionnaires to the students that have been participated in the Arabic debate competition as sample. The sample was chosen from all faculties and the study was practiced to 40 students. The results of this study show that the Arabic debate is effective to develop the speaking skills among participants as the entire sample have benefited a lot from the debates to develop and enhance their speaking skills. The benefits include all four aspects of the standard develop of speech, such as intellectual, linguistics, audio, and interactive aspects. The researcher draws some suggestions for maximizing the role and contribution of debates to improve the speaking skills of the students especially and to all the universities and institutions in general. Lastly, the study suggested that every student of Arabic Language in particular and whoever interested in teaching and learning it in general, to take the selected strategies as their guideline in enhancing speaking skill level.